Asset prices and financial imbalances in CEE countries: Macroeconomic risks and monetary strategy - Zoltán Szalai (Magyar Nemzeti Bank, 2011)
Modern central banks have adopted a 'risk management' approach in assessing and presenting risks to macroeconomic stability. This paper seeks to contribute to the improvement of central banks' current strategies for Central and Eastern European countries, first by assessing the potential size of macroeconomic risks, and secondly by empirically relating these risks to certain selected financial variables. Our results suggest that risks to GDP and the Price Level are significantly higher than commonly supposed based on a normal distribution of their cyclical components. However, relating these risks to the selected financial variables generated mixed results and is rarely significant in economic terms. We conclude that central banks currently risk underestimating the probability of large deviations in GDP and Price Level from their trends. A combination of financial variables and the inclusion of international financial variables could result in more significant results than the ones used separately in this study, when looking for useful indicators of such events.
Keywords: E44; E52; E58; 330; central bank policy; financial imbalances; GDP-at-risk; CPI-at-risk